2017
DOI: 10.2214/ajr.16.17582
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Image-Guided Cryoablation of Hepatic Tumors: Single-Center Experience With Intermediate to Long-Term Outcomes

Abstract: OBJECTIVE The purpose of this article is to report our intermediate to long-term outcomes with image-guided percutaneous hepatic tumor cryoablation and to evaluate its technical success, technique efficacy, local tumor progression, and adverse event rate. MATERIALS AND METHODS Between 1998 and 2014, 299 hepatic tumors (243 metastases and 56 primary tumors; mean diameter, 2.5 cm; median diameter, 2.2 cm; range, 0.3–7.8 cm) in 186 patients (95 women; mean age, 60.9 years; range, 29–88 years) underwent cryoabla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 48 publications
1
41
1
2
Order By: Relevance
“…Although current series mainly including liver metastases of colorectal tumors are available, there are no prospective randomized studies. Two current series including 742 liver tumors yielded acceptable results regarding safety in tumors < 4 cm with grade ≥ 3 complications in 5.8 -8.7 % of interventions but a significant increase in the complication rate in larger lesions [30,31]. There are significant differences with respect to results, i. e., Littrup et al showed a local progression rate similar to that of other methods of 11.1 % after 1.8 years in metastases of colorectal tumors [30] while the progression rate reported by Glazer et al after 2.5 years was 25.4 % [31].…”
Section: Livermentioning
confidence: 98%
See 2 more Smart Citations
“…Although current series mainly including liver metastases of colorectal tumors are available, there are no prospective randomized studies. Two current series including 742 liver tumors yielded acceptable results regarding safety in tumors < 4 cm with grade ≥ 3 complications in 5.8 -8.7 % of interventions but a significant increase in the complication rate in larger lesions [30,31]. There are significant differences with respect to results, i. e., Littrup et al showed a local progression rate similar to that of other methods of 11.1 % after 1.8 years in metastases of colorectal tumors [30] while the progression rate reported by Glazer et al after 2.5 years was 25.4 % [31].…”
Section: Livermentioning
confidence: 98%
“…Two current series including 742 liver tumors yielded acceptable results regarding safety in tumors < 4 cm with grade ≥ 3 complications in 5.8 -8.7 % of interventions but a significant increase in the complication rate in larger lesions [30,31]. There are significant differences with respect to results, i. e., Littrup et al showed a local progression rate similar to that of other methods of 11.1 % after 1.8 years in metastases of colorectal tumors [30] while the progression rate reported by Glazer et al after 2.5 years was 25.4 % [31]. In a separate study including 59 patients with 151 liver metastases of colorectal carcinomas, Littrup's group reports an average survival rate of 23.6 months after cryotherapy [32].…”
Section: Livermentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the intraprocedural monitoring of ice ball formation minimizing the chance of harming adjacent critical structures, the limited ice ball extension beyond the liver into the diaphragm or body wall with less pain and injury than RFA [47], cryoablation could be preferred to RFA or MWA to treat hepatic masses close to critical structures, such as the diaphragm, chest wall, heart, lung, gallbladder, and biliary tree [48,49], with better results for lesions less than 4 cm in size [50] (Figure 2).…”
Section: Cryoablationmentioning
confidence: 99%
“…One single-center study reviewed cryoablation of 299 primary and metastatic hepatic tumors; however, only 6 were cholangiocarcinoma. 44 Similarly, another study of cryoablation of hepatic tumors included 39 tumors of which only 3 were IHC. 45 Both studies concluded that cryoablation is an effective treatment option for both primary and metastatic liver tumors, but no survival data were reported for IHC.…”
Section: Cryoablation Of Intrahepatic Cholangiocarcinomamentioning
confidence: 99%